Toward the digitalisation of the organisational learning capability to enhance organisational performance - Akaraeen, Mohamed; Al-Ashaab, Ahmed (World Scientific and Engineering Academy and Society (WSEAS), 2021)
Public organisations provide training to enhance their employee’s capabilities to provide better services. Public organisations use different learning methods to enhance their employee’s skills and service offering. Therefore, public organisations are considering different learning programmes such as classroom training, coaching, mentoring etc. For the organisations to be effective in providing the learning programs to their employees, there is a need to have an approach to support these efforts. This study suggests that Organisational Learning Capability (OLC) is the right approach to do that. This is because OLC facilitates the learning process. The study proposes an OLC model consists of the key elements that represent the definition of OLC; these are the learning processes, enablers, influential factors. This paper explores how organisations can bridge the gap between investments in learning initiatives and improvement in service provision in public organisations. The context of this study is the creation of a set of learning and development programs in the public services organisations. The top OLC model helps to define all other learning programmes where the coaching learning program is presented in this paper.
Keywords: Learning process in organisations; Coaching learning programme; Public services organisations; Organisational Learning capability